Defining Taiwanese children's health literacy abilities from a health promotion perspective. (December 2017) - Liao, Li-Ling; Liu, Chieh-Hsing; Cheng, Chi-Chia; Chang, Tzu-Chau
Background: Health literacy is related to health inequality, health behaviors, and health status. Globally, health literacy has primarily focused on adults and has been based on the medical model. It is necessary to understand children's life experiences as they relate to health; thus, this study attempted to evaluate and describe the health literacy abilities of sixth-graders in Taiwan. Methods: Interviews were conducted with 10 teachers and 11 caregivers, and focus groups were conducted with 32 children. Health literacy abilities corresponding to real-life situations were identified from life skills and the Taiwanese Curriculum Guidelines for health education. Three expert meetings were held to redefine children's health literacy using a health promotion perspective and confirmed indicators. Results: An operational definition of three aspects of children's health literacy and 25 abilities was proposed: 11 functional health literacy abilities (e.g. understands the connection between personal health care behaviors and health); seven interactive health literacy abilities (e.g. obtains and understands information from various channels); and seven critical health literacy abilities (e.g. analyzes the relationship between personal needs and diet choices for a balanced diet). These indicators cover 10 health education categories. Conclusions: These findings highlight the importance of understanding Taiwanese children's health literacy, and the urgency of developing an appropriate measurement tool. The definition and indicators in this study were identified using a child-centered approach focusing on children's real-life experiences. The result serves as a solid basis for the development of the Taiwan Children's Health Literacy Scale, and provides information for the decision-making sector on health education.